(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2023)
Various structural factors that contribute to damage during an earthquake are vertical irregularities, irregularities in strength and stiffness, mass irregularities, torsional irregularities, and so on. Over the past decade, performance-based design (PBD) procedures have become one of the most critical areas in earthquake engineering. The pushover procedure is divided into two parts; the first is the displacement target for the erected building. The target is the estimated displacement of the top of the building when exposed to the design earthquake excitation. Then a pushover analysis is carried out on the building until the top removal is equal to the target displacement. Second is the type of controlled force in which the total amount of force acting is estimated and applied to the structure, and analysis is carried out. The various performance levels for a building are expressed in terms of the base shear carried versus the roof displacement. If all the plastic hinges formed are within the CP limit, the structure is said to be safe. On the other hand, if the plastic hinge formed exceeds the CP limit, the structure is said to have collapsed. This paper proposes a 2D reinforced concrete frame with three models with variations of vertical irregularity. This paper aims to see the nonlinear behavior of reinforced concrete frames with vertical irregularities through the pushover method using SAP2000 software. Furthermore, the analysis results show that the skeleton is susceptible to increasing vertical irregularity. As the vertical irregularity increases, the percentage of the plastic hinge crossing the boundary increases. The analysis results also show that model 2 has better behavior.